The Mayor's ballyhoo, says who? a descriptive study on the Calauan controversy and the dynamics of attribution, social schemata and stereotypes - Frando, Genevive V.
This study entitles, The Mayor's Ballyhoo, Says Who? : A Descriptive Study on the Calauan Controversy and the Dynamics of Attribution, Social Schemata and Stereotypes had a general objective of exploring the role of media and communication in the formation of schemata and stereotypes regarding Mayor Sanchez, Calauan, Laguna and its people as an aftermath of Sanchez's conviction for rape. The study's specific objectives were (1) to determine existing schemata and stereotypes regarding Mayor Sanchez, Calauan and Calaueños among a)Residents and b)Non-Residents of the town; (2) to determine sources of these schemata and stereotypes such as: a)Media remembered as sources; and (3) to assess the attitudes and opinions formed through the cognitive processing of the information offered by TV and Print Media regarding the Calauan controversy. In the formulation of framework, the researcher utilized an amalgam of various theories such as the Schema theory, Stereotypes, Attribution theory, Dependency theory, and the Agenda-Setting Function. The main findings of the study state that schemata regarding Sanchez come in varied forms among Calaueños. Definitely, it was found out that non-Calaueños hold negative schemata about Sanchez. Mayor Sanchez has a relatively bad image among Calaueños and non-Calaueños. Only a very few number of Calaueños who are Sanchez loyalists perceive him in a positive way. Calauan's image to both Calaueños and non-Calaueños appears to be a quiet and sleepy town. There exist different schemata and stereotypes regarding Calauan, Laguna. Likewise, there exist various forms of schemata and stereotypes regarding Calaueños. But it was ascertained that they are known to be sweet, diligent, loving people to both Calaueños and non-Calaueños. The negative schemata which were also shared by both residents and non-residents of the town were their being passive, and submissive to almost anything that happens in their town. Apparently, both Calaueños and non-Calaueños believed that that media tended to sensationalize news reports such as the Calauan Controversy. They asserted that the media played is a biased role in presenting the Calauan issue. However, both Calaueños and non-Calaueños also believe that the media performed a very important role in exposing the Calauan case and in prompting the authorities to quickly act against the perpetrators of the rape-slayings. Non-Calaueños reiterated that Mayor Sanchez's rape-murder case was an isolated one. Their attitudes and opinions were not affected by the news reports offered by media. On the other hand, Calaueños were convinced that these are an exact opposite. Evidently, it is worth noting that there were several Calaueños who felt they were discriminated just because they're from Calauan.